Media Aminoacid Profile During In Vitro Co-Culture of Human Pre-Implantation Embryos on Monolayer of Fresh or Cryopreserved Cumulus and Granulosa Cells - Petrushko, Marina P.; Pinyaev, Vladimir I. (Problems of Cryobiology and Cryomedicine, 2016)
Co-culturing with the cumulus and granulosa cells (CGC) provide a microenvironment which can ensure the normal growth and development of human pre-implantation embryos in vitro. Examining the quantitative and qualitative compositions of this environment is of an important value to produce the systems to culture human embryos in vitro. The paper described the human embryos of the fifth day of development (blastocyst stage), monolayer culture of cryopreserved and freshly isolated CGC. We investigated the influence of culturing on monolayer of freshly isolated and cryopreserved CGC on morphokinetic characteristics of human pre-implantation embryos obtained in vitro as well as the amino acid profile of the culturing media. It has been found that cryopreservation does not affect the ability of CGC to support the development of pre-implantation embryos and improves their quality. There was determined the difference in amino acid composition of the standard medium of those for co-culturing on monolayer of either native or cryopreserved culture and cumulus granulosa. The presence of CGC changes the biochemical profile of culturing medium by increasing the content of the amino acids such as tryptophan, proline, valine, ornithine and glutamine. Â  Probl Cryobiol Cryomed 2016; 26(2):124-132.